(3JgPjH GdQLGd aj CSeGA GdQLGds - (3Ndjd Hf CjHc Hf YHO Gddg GdUaOj, UdGM GdOjf , J (B764 (3g` s ((3eMeO Hf EHQGgje Hf ZfGje Hf GdegfOS s)
(3ChdgG (B:s
(3ef HGH GdcGa ef Gdcfi s
(3BNQgG (B:s
(3Edi Ce eSdeI s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B34s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B1274 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B100 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs